Polymerase Chain Reaction Testing of Vitreous in Atypical Ocular Syphilis. (June 2013) - Troutbeck, Robyn; Chhabra, Ramandeep; Jones, Nicholas P.
Abstract Purpose: To illustrate the diagnostic importance of syphilis PCR testing on intraocular fluid for atypical presentations. Methods: Retrospective case series. Results: Two cases of atypical intraocular inflammation were confirmed by PCR testing of vitreous for Treponema pallidum DNA. Conclusions: Ocular syphilis may be present in atypical fashion, and delayed treatment may lead to irreversible visual loss. Sampling of intraocular fluid for PCR testing may confirm diagnosis and lead to appropriate treatment.